Elevated morbidity and mortality in patients with chronic idiopathic hypophosphatemia: a nationwide cohort study - Kim, Kyoung Jin; Song, Ji Eun; Kim, Ji Hyun; Hong, Namki; Kim, Sin Gon; Lee, Juneyoung; Rhee, Yumie (Frontiers in Endocrinology, 2023)
Background: Chronic idiopathic hypophosphatemia (CIH) induced by X-linked hypophosphatemic rickets or tumor-induced osteomalacia is a rare inherited or acquired disorder. However, due to its rarity, little is known about the epidemiology and natural course of CIH. Therefore, we aimed to identify the prevalence and long-term health outcomes of CIH patients. Methods: Using the Korean Health Insurance Review and Assessment claims database, we evaluated the incidence of hypophosphatemia initially diagnosed from 2003 to 2018. After excluding secondary conditions that could change serum phosphorus levels, we identified 154 patients (76 men and 78 women) with non-secondary and non-renal hypophosphatemia. These hypophosphatemic patients were compared at a ratio of 1:10 with age-, sex-, and index-year-matched controls (n = 1,540). Results: In the distribution of age at diagnosis, a large peak was observed in patients aged 1–4 years and small peaks were observed in ages from 40–70 years. The age-standardized incidence rate showed non-statistically significant trend from 0.24 per 1,000,000 persons in 2003 to 0.30 in 2018. Hypophosphatemic patients had a higher risk of any complication (adjusted hazard ratio [aHR], 2.17; 95% confidence interval [CI], 1.67–2.69) including cardiovascular outcomes, chronic kidney disease, hyperparathyroidism, osteoporotic fractures, periodontitis, and depression. Hypophosphatemic patients also had higher risks of mortality and hospitalization than the controls (aHR, 3.26; 95% CI, 1.83–5.81; and aHR, 2.49; 95% CI, 1.97–3.16, respectively). Conclusion: This first nationwide study of CIH in South Korea found a bimodal age distribution and no sex differences among patients. Hypophosphatemic patients had higher risks of complications, mortality, and hospitalization compared to age- and sex-matched controls.